A frequency and pattern reconfigurable asymmetric ground antenna on flexible polyimide material for LTE, Wi-Fi, WLAN and fixed satellite applications. (19th June 2020) - Lakshmi, M L S N S; Madhav, B T P; Khan, Habibulla; Kishore, P V V
Abstract: In this work, an asymmetric ground structured hybrid reconfigurable antenna is designed, on a polyimide substrate material. The antenna model occupies dimensions of 43 × 28 × 0.2 mm, with two F-shaped slots and a U-shaped slot in the radiating structure. The antenna provides an impedance bandwidth of 44% (2.3–3.8 GHz), 12% (4.5–5.1 GHz), and 7% (6.3–6.8 GHz) at three resonant frequencies. Parametric analysis with respect to dimensional parameters is conducted in order to optimize the performance characteristics of the antenna. The asymmetric ground with slots on the radiating structure provides frequency and pattern reconfigurability by means of the placement of BAR 64 diodes, and tunability by means of switching conditions. The proposed antenna provides frequency and pattern reconfigurability in 'S' and 'C' bands for LTE, Wi-Fi, WLAN, and fixed satellite applications. A peak realized gain of 4 dB, and anefficiency of more than 74% is achieved at the fundamental resonant band of the antenna. Four-state frequency reconfigurability, and two-state pattern reconfigurability is achieved with beam steering at 30° and 330° in the azimuthal plane. The flexible behavior of the antenna is also analyzed at various bending angles in X and Y-directions, and found to show good agreement with simulation results obtained from Ansys HFSS tool, and with the measurement results of a combinational analyzer in the anechoic chamber.